The determination of the incidence of domestic violence (2003)
The magnitude of domestic violence is increasing in an unprecedented rate. Most of the cases have not been reported and documented since this family problem is considered as a private matter. This study was conducted to unveil the factors that contribute to the incidence of domestic violence. The sources of data were from the 2001 records and files of DSWD and women's desk police station, and interview of the victims or friends and neighbors of the victims. There were a total of two hundred ten (210) families or cases involved in the study, with one hundred seven (107) of them had the incidence of domestic violence. Stepwise, Multiple Regression was used to statistically determine the hypothesized relationship between the dependent and independent variables. Results indicated that most of the victims were females; both the abusers and the victims were young and completed high school; and more abusers were employed than the victims. Majority of the victims' housing was shanty type with the average number of two bedrooms and five dwellers. Domestic violence is more prevalent in shanty type of dwelling, apparently because this house structure does not provide adequate security for the vulnerable members of the family. In addition, the incidence happened more frequently in Metro Manila. Males have a higher tendency to be abusive than their female counterparts because of their grater ability to injure physically. Females with lower educational attainment, younger, and employed were most likely to be abused. On the other hand, males who are married, and unemployed tended to be abusive. Incidence of domestic violence particularly incest is higher if the spouse is living away from the family. Some of the recommendations forwarded include skills enhancement course for actual or potential victims to be integrated in the programs of school and government agencies to help them develop assertiveness and self confidence; equip the poor households with entrepreneurial skills to augment their economic conditions and thus, improve their housing; collaborative effort of National Statistics Office, Department of Social Welfare and Development, Department of Justice, Department of Health and Police Station women's desk in documenting the cases of domestic violence; integration of gender sensitivity in the elementary and secondary curriculum in MAKABAYAN subject and in Social Science in tertiary level, And create awareness on the importance of mother's presence at home in safeguarding female young children against incest.
Keywords: Family violence